Hess Collection - Ronte, Dieter; Hess, Donald M.; The Hess Collection, Napa (New York : Harry N. Abrams Inc. Publishers, 1989)
Abakanowicz, Magdalena ; Armando ; Bacon, Francis ; Baselitz, Georg ; Boyle Family ; Gertsch, Franz ; Gilbert & George ; Iseli, Rolf ; Jensen, Alfred ; Kirkeby, Per ; Kriesche, Richard ; Louis, Morris ; Maler, Leopoldo M. ; Mehring, Howard ; Michaux, Henri ; Motherwell, robert ; Raetz, Markus ; Rainer, Arnulf ; Richter, Gerhard ; Robbins, Bruce ; Soutter, Louis ; Starnos, Theodoros ; Stella, Frank ; Vedova, Emilio ; Bill, Max ; Glarner, Fritz ; Graeser, Camille ; Loewensberg, Verena ; Lohse, Richard Paul
boek